Pemanfaatan Tanaman Eceng-Ecengan (Ponteridaceae) sebagai Agen Fitoremediasi dalam Pengolahan Limbah Krom - Yola Desnera Putri; Holis Abdul Holik; Ida Musfiroh; Anisa D. Aryanti (Indonesian Journal of Pharmaceutical Science and Technology, 2014)
Water pollution caused by waste chrome leather tanning industry at Sukaregang, Garut Regency should be done by phytoremediation technique using plants from Ponteridaceae family. This research needs to know the level of absorption of Ponteridaceae plants and determine which one is the most effective to absorb chrome. The phase of this research is by gathering materials and determination of the Ponteridaceae plants, waste treatment with phytoremediation in 21 days, and analysis of chromium levels with an atomic absorption spectrophotometer. The absorption capacity of Eichhornia crassipes Solm., Heteranthera peduncularis and Monochoria vaginalis are 1.5395; 0.5728, and 0.1057 µg/g. Based on the Duncan test, it is concluded that Eichhornia crassipes Solm. is the most effective among them with the highest ability to absorb metal chrome tannery wastes. Keywords: Chrome, Eichhornia crassipes Solm., Heteranthera peduncularis, Monochoria vaginalis, phytoremediation